Globalisation, Economic Growth, and Spillovers: A Spatial Analysis. (August 2019) - Ahmad, Mahyudin
This article seeks to deepen our understanding of the globalisation–growth nexus as it extends the investigation to using a spatial econometric approach, hitherto rarely used in the globalisation literature. The objective of the article is to uncover not only the significant growth effects of globalisation but also its possible spillover effects onto neighbouring countries. Using a panel data set of 83 countries across a 30-year period and via a spatial autoregressive panel data method, this article estimates a standard growth model augmented with a parameter to capture the countries' spatial dependence, whilst controlling for globalisation indices. The findings indicate a positive effect of economic globalisation, which is dependent upon the political settings in the countries under study. The spillover effects of globalisation across neighbouring countries are shown, both in geographical and institutional spheres. The article concludes with some policy recommendations. JEL: F63, C31